Effect of polyalcohols on the anticorrosive behaviour of alkyd coatings prepared with drying oils - Hadzich A. (2020)
Alkyd paints contain resins derived from vegetable oils. Alkyd resins have regained their importance since they are mostly composed of bio-based constituents recovered from biofuels production and agro-industrial waste. The anticorrosive performance of medium alkyd paints modified with Sacha inchi and linseed oils, and different ratios of glycerol and pentaerythritol, were compared by accelerated corrosion tests (Salt Fog and Sulphur Dioxide tests). This study focuses on comparing the effect of polyalcohol and oil type on physicochemical properties of resin solutions and cured films, and consequently, on the anticorrosive behaviour of paints prepared with the resins under study. Results showed that the mixture of pentaerythritol and Sacha inchi oil improves alkyd resin properties and enhance the anticorrosive performance of alkyd paints in accelerated weathering tests. © 2020 Elsevier B.V.